Copper nanoparticle-deposited graphite felt electrodes for all vanadium redox flow batteries. (15th October 2016) - Wei, L.; Zhao, T.S.; Zeng, L.; Zhou, X.L.; Zeng, Y.K.
Highlights: Copper nanoparticle is proposed as electrocatalyst for VRFBs for the first time. Propose a binder-free copper nanoparticle decorated electrode. The energy efficiency is up to 80.1% at 300 mA cm −2, enhancing more than 17%. High stability and capacity retention are achieved by battery with copper catalyst. Abstract: A copper nanoparticle deposited graphite felt electrode for all vanadium redox flow batteries (VRFBs) is developed and tested. It is found that the copper catalyst enables a significant improvement in the electrochemical kinetics of the V 3+ /V 2+ redox reaction. The battery's utilization of the electrolyte and energy efficiency are found to be as high as 83.7% and 80.1%, at a current density of 300 mA cm −2, which are 53.1% and 17.8% higher than those of the battery without the catalyst. Moreover, the present battery shows a good stability during the cycle test. The results suggest that the inexpensive copper nanoparticle catalyst without tedious preparation process offers a great promise for VRFB application.